2015
DOI: 10.7243/2055-091x-2-9
|View full text |Cite
|
Sign up to set email alerts
|

Role of ginger (zingiber officinale) against metalaxyl induced hepatotoxicity in male albino rats: a histological and immunohistochemical study

Abstract: Background: Metalaxyl is a fungicide used to control soil-borne fungal diseases on fruits, cotton, soy bean, peanuts and grasses. Food contamination with metalaxyl is a worldwide problem especially in developing countries. Ginger has antioxidant properties. Aim of the work: To elucidate the histological alterations that may occur in the liver tissue of rat by metalaxyl and to investigate the role of ginger supplementation against these alterations. Materials and methods: Thirty healthy adult male albino rats w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 30 publications
(37 reference statements)
1
8
0
Order By: Relevance
“…A similar observation was made for ethoprophos, an insecticide that has been shown to induce hepatotoxicity in mice [33]. e use of the fungicide active principles metalaxyl and copper oxide was also associated with elevated ALT activity in the farmers, and corroborate previous reports on hepatotoxicity of these chemicals in rodents [34,35]. In general, fungicides, with a cumulative frequency of 20% (as opposed to 7% for insecticides) were the most represented pesticide group associated with hepatotoxicity among farmers.…”
Section: Supplementary Materialssupporting
confidence: 88%
“…A similar observation was made for ethoprophos, an insecticide that has been shown to induce hepatotoxicity in mice [33]. e use of the fungicide active principles metalaxyl and copper oxide was also associated with elevated ALT activity in the farmers, and corroborate previous reports on hepatotoxicity of these chemicals in rodents [34,35]. In general, fungicides, with a cumulative frequency of 20% (as opposed to 7% for insecticides) were the most represented pesticide group associated with hepatotoxicity among farmers.…”
Section: Supplementary Materialssupporting
confidence: 88%
“…Pretreatment with ginger extract 9GE) markedly improved the histological structure of the liver cell membrane and decreased the release of aminotransferases from hepatocytes, in addition to decline the oxidative stress induced by APAP. These results may be attributed to the antioxidant effect of ginger and its capability to maintain the cell membrane integrity (EI-Ghonaimy, 2015). The antioxidant effect of ginger is associated with its active ingredients such as gingerols and shogaols which consider the most important components present in ginger root (Mekuriya and Mekibib, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that ginger administration improved the histopathological changes and increased the glycogen and proteins contents in the liver of rats treated with 7,12-dimethylbenz(a)anthracene (DMBA) and fungicide Metalaxyl benzenoid. [ 6 , 26 ].…”
Section: Discussionmentioning
confidence: 99%